Depression, low self-esteem and mindfulness. - Fennell, M (2004)
Negative biases in processing information about the self have long been recognised as a central feature in the development and maintenance of clinical depression. In practice, however, it may not be easy to distinguish between patients whose negative thinking about the self is primarily an aspect of current mood state, and those for whom it represents a reflection of more enduring issues (low self-esteem). The paper speculates that, in both cases, metacognitive awareness (acceptance of the idea that thoughts, assumptions and beliefs are mental events and processes rather than reflections of objective truth) may be an important precursor to active engagement in therapy on the part of the patient, and considers what aspects of cognitive therapy might be used to promote it in clinical practice.